Match analysis in volleyball: a systematic review - Silva, M.; Marcelino, R.; Lacerda, D.; João, P. V. (Montenegrin Journal of Sports Science and Medicine, 2016)
The present article aims to review the available literature on match analysis in adult male Volleyball. Specific key words "performance analysis", "match analysis", "game analysis", "notational analysis", "tactical analysis", "technical analysis", "outcome" and "skills" were used to search relevant databases (PubMed, Web of Science, SportDiscus, Academic Search Complete and the International Journal of Performance Analysis in Sport). The research was conducted according to PRISMA (Preferred Reporting Items for Systematic reviews and Meta analyses) guidelines. Of 3407 studies initially identified, only 34 were fully reviewed, and their outcome measures extracted and analyzed. Studies that fit all inclusion criteria were organized into two levels of analysis, according to their research design (comparative or predictive) and depending on the type of variables analyzed (skills and their relationship with success, play position and match phase). Results show that from a methodological point of view, comparative studies where currently complemented with some predictive studies. This predictive approach emerged with the aim to identify the relationship between variables, considering their possible interactions and consequently its effect on team performance, contributing to a better understanding of Volleyball game performance through match analysis. Taking into account the limitations of the reviewed studies, future research should provide comprehensive operational definitions for the studied variables, using more recent samples, and consider integrating the player positions and match phase contexts into the analysis of Volleyball.